A CRITICAL ANALYSIS OF DISTRIBUTIVE JUSTICE IN THE CARBON FUND DISTRIBUTION POLICY OF THE FOREST CARBON PARTNERSHIP FACILITY (FCPF) IN MAHAKAM ULU REGENCY, EAST KALIMANTAN - Dhespy Tandi Pasauran; Muhammad Dzaudan Sani; Muhammad Hairul Saleh; Sonny Sudiar (Bajang Institute, 2026)
The distribution of benefits from global carbon financing schemes continues to face serious challenges regarding fairness for regions that make substantial contributions to forest conservation. This study examines the carbon fund allocation policy of the Forest Carbon Partnership Facility (FCPF) in East Kalimantan Province, focusing on Mahakam Ulu Regency, which maintains 86.95% forest cover yet reportedly receives a disproportionate allocation. A qualitative case study approach was employed through document analysis, secondary data review, and media-based interviews with local stakeholders. The theoretical framework draws on distributive justice based on contribution, rights, and needs, with indicators of proportionality, transparency, institutional capacity, and stakeholder participation. Using Miles and Huberman’s (1994) interactive analysis model, findings indicate a misalignment between Mahakam Ulu’s ecological contribution and the funding received only IDR 1.305 million per km² of forest in the first payment period. Contributing factors include a lack of transparency in the Benefit Sharing Plan (BSP) allocation formula, limited local institutional capacity, and the exclusion of three villages from the beneficiary list. This study recommends reformulating allocation criteria to recognize passive conservation value, strengthening local capacity, and improving distribution transparency.